Effects of Dietary Supplementation of Garlic (Allium sativum) powder on Growth Performance and Carcass Characteristics of Broilers - Makwana, RB; Bhagat, SR; Parikh, SS; Savaliya, BD; Jadav, CN (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was carried out for six weeks to investigate the effects of adding graded levels (0, 0.1 and 0.5%) of garlic (Allium sativum) powder to the basal experimental diet on the growth performance and carcass characteristics of broiler chicks. One hundred and eighty (n = 180) day old unsexed white commercial broiler chicks (Cobb-400) were randomly distributed into three dietary treatments of 60 birds/treatment and each treatment contained 4 replicates (15 birds/replicate). The dietary treatments were controlled basal diet (T1), and a diet supplemented with garlic powder at 0.1% (T2) and 0.5% (T3). Daily feed intake, weekly body weight, and residue leftover were recorded to calculate the feed conversion ratio (FCR). At the end of the experiment, six birds from each group were sacrificed to determine the carcass characteristics. Results revealed that dietary supplementation of 0.1% garlic powder (T2) significantly (p <0.01) improved body weight, body weight gain, feed intake and FCR as compared to birds supplemented with 0.5% garlic powder (T3) and control diet (T1). Dietary supplementation of 0.1% garlic (T2) resulted in significant (p <0.05) improvement in dressed yield as compared to T3 and T1. On the other hand, comparable (p >0.05) effect was observed on shrinkage loss, blood loss, feather loss, eviscerated yield and relative weight of giblet. Thus, dietary supplementation of 0.1% garlic powder had beneficial effects on growth performance and dressed yield of broiler chicks.